Speech and Language Therapy Interventions Throughout the Oral Cavity Cancer Pathway: A Scoping Review - Kate Baker; Sinead Rothrie; Grainne Brady; Susanne Cruickshank; Justin Roe (Advances in Communication and Swallowing, 2026)
Objective The anatomical location of oral cavity cancer (OCC), plus its usual treatment options of surgery with or without (chemo-)radiotherapy, may impact profoundly on speech and swallowing outcomes. The aim of this scoping review was to identify and summarise speech and language therapy (SLT) intervention types and service delivery models employed in OCC over the last 25 years, in order to summarise current practice. Method Systematic searches were conducted in three databases and via Google Scholar for papers published from 2000 to November 2025. The inclusion criteria were SLT-led interventions and OCC. Articles relating to other HNCs, therapy carried out by other healthcare professionals, articles solely reporting outcomes and non-English-language publications were excluded. Results A total of 443 publications were retrieved, resulting in 14 papers that were analysed: five focused solely on swallowing, three on speech alone and five on both functions. One paper described swallowing and trismus intervention. The most common study designs were single group cohorts/case series (57%, n = 8). Oromotor exercises, other direct therapy and compensatory strategies were regularly used for both speech and swallowing. There was significant variation in the timing, frequency and intensity of therapy offered. Conclusion SLT-led speech and swallowing interventions typically include a combination of oromotor exercises, other direct therapy and compensatory strategies. The quality of evidence relating to swallowing intervention is higher than that for speech. While long-established interventions form the basis of rehabilitation interventions, new approaches to SLT intervention are being trialled.